Terapi Relaksasi Benson untuk Menurunkan Tekanan Darah pada Hipertensi dalam Asuhan Keperawatan Keluarga di Desa Cihanjuang Rahayu: Studi Kasus - M. Iqbal Sutisna; Elsa Sandari Ayudia Nirwanti; Syfa Rahma Nur Alifiyah; Mochamad Gibran Adrian Kusumah; Amelia; Sri Winangsih (LPPM Akbid Harapan Ibu Pekalongan, 2026)
Hypertension is a condition where blood pressure remains above normal for a long period, influenced by age, psychological stress, genetic factors, unhealthy lifestyle, and sleep disorders. Uncontrolled Hypertension can lead to complications, one of which is stroke. Non-adherence to pharmacological therapy becomes an obstacle to blood pressure control, thus non-pharmacological alternatives are needed. Benson Relaxation therapy is a deep breathing relaxation technique combined with belief and has the potential to lower blood pressure. This Family Nursing Care aims to determine the effectiveness of Benson Relaxation therapy in reducing blood pressure in hypertensive patients. The method used is a case study with an evidence-based nursing practice approach. The therapy is administered once a day for three days with a duration of 15–20 minutes. The results show a decrease in blood pressure in clients with Hypertension after the implementation of Benson relaxation therapy. Benson Relaxation therapy is recommended to be applied in family nursing care and developed in community settings to broaden the scope of Interventions and support Hypertension control in the community.